(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Starting techniques are major disciplines in swimming to get extra advantage while taking the start, especially in freestyle, butterfly, and breaststroke. After reviewing various research articles and studies, a study was conducted on a kinematical comparison of two different starting techniques in swimming among professional swimmers. Method: Five male swimmers of dolphin academy, Hoshangabad who have participated at the national level were selected as subjects of the study. The videography technique through Canal D camera was used with 30 frames frequency/ second and examined in the horizontal plane (sagittal plane) from the left side was employed to gather the performance in track and grab starts. Analysis: In order to photographic sequence, selected kinematic variables were obtained and analysed through Kinovea Software (Suggested Hey J. G., 1999) to assess the centre of gravity of the body during set position and releasing time.